A 72 years of temporal analysis through geometric morphometrics detects phenotypic variation in populations of Triatoma infestans (Klug, 1834) - Paschoaletto e outros, Letícia (Acta Biológica Paranaense, 2020)
<htm> A 72 years of temporal analysis through geometric morphometrics detects phenotypic variation in populations of Triatoma infestans (Klug, 1834)</htm>